Risk of cesarean after induction of labor in twin compared to singleton pregnancies. (June 2019) - Loscul, C.; Schmitz, T.; Blanc-Petitjean, P.; Goffinet, F.; Le Ray, C.; ,
Abstract: Objective: To assess the risk of cesarean delivery after induction of labor in twin compared with singleton pregnancies. Study design: This retrospective multicenter study compared data from two nationwide prospective cohorts: one of twin pregnancies established from February 2014 through March 2015 (JUMODA cohort), and the other of singleton pregnancies in November and December 2015 (MEDIP cohort). This study includes all women in both cohorts who had labor induced at ≥ 35 weeks of gestation, with a live fetus in cephalic presentation (Twin 1 for the twin pregnancies). Multivariate analyses with multilevel logistic regression models were used to study twin pregnancy as an independent risk factor for cesarean delivery, overall and stratified for parity and Bishop score. Results: The outcomes of 1995 twin births after induction of labor were compared to those of 2771 induced singleton births. The cesarean rate differed significantly between the two populations and was higher in twins (23% in twins vs 19.4% in singletons, P = 0.002). After adjustment for factors associated with cesareans, twin pregnancy was independently associated with it (aOR = 1.8, 95% CI 1.4–2.2). Conclusion: Twin pregnancy appears to be an independent risk factor for cesarean births after induction of labor, but more than three-quarters of inductions culminated in vaginal delivery.